Distribution of serological response to Burkholderia pseudomallei in swine from three provinces of Vietnam - Norris, M.H.; Hang Thi Thu Tran; Walker, M.A.; Bluhm, A.P.; Zincke, D.; Trinh Thanh Trung; Nga Vu Thi; Ngoc Pham Thi; Schweizer, H.P.; Unger, Fred; Blackburn, J.K.; Nguyen Thi Thu Hang (MDPI, 2020)
(1) Background: Burkholderia pseudomallei is an environmentally mediated saprophytic pathogen that can cause severe disease in humans. It is well known that B. pseudomallei survives in tropical moist soil environments worldwide, but melioidosis is gaining recognition as a public and veterinary health issue in Vietnam. The contribution of animals to human disease is unknown, necessitating further investigation. (2) Methods: Swine sera were collected from two populations, one grazing and one commercially farmed, from three provinces in Vietnam. ELISAs utilizing B. pseudomallei capsular polysaccharide (CPS), outer polysaccharide (OPS), and Hcp1 protein were used to screen serum samples. Positive samples were mapped to the commune level. Seroprevalence calculations and pig population estimates were used to approximate number of swine exposures per commune. (3) Results: Grazing pigs from Hoa Binh had significantly higher seropositivity levels (11.4%, 95% CI: 9.7–13.1) compared to farmed pigs from Ha Tinh and Nghe An (4%, 95% CI: 3.3–4.7). Average swine seropositivity rates were ~6.3% (95% CI: 5–7.9), higher than previously identified in Vietnam (~0.88%). (4) Conclusions: Initial serological sampling identified a significant number of seropositive and potential melioidosis infections occurring in swine in Vietnam. This work is a critical step in understanding the role swine may play in the epidemiology of human melioidosis in Vietnam.